2022
DOI: 10.3390/ijms232012643
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and Therapeutic Applications of Esculetin

Abstract: Esculetin is a coumarin compound, which belongs to the class of benzopyrone enriched in various plants such as Sonchus grandifolius, Aesculus turbinata, etc. Free radicals lead to the development of oxidative stress causing inflammation, arthritis, cancer, diabetes, fatty liver disease, etc. These further reduce the efficacy of anticancer drugs, activate inflammatory signaling pathways, degrade joints and cartilage, and disrupt the glycemic index and normal function of liver enzymes. For instance, the current … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 118 publications
0
19
0
Order By: Relevance
“…Esculetin has been shown to have therapeutic effects in a variety of conditions, including free radical scavenging, suppression of various dysregulated transcription factors in cancer, and effects on inflammatory pathways involved in diseases such as arthritis, glycaemic index, and fatty liver syndrome. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esculetin has been shown to have therapeutic effects in a variety of conditions, including free radical scavenging, suppression of various dysregulated transcription factors in cancer, and effects on inflammatory pathways involved in diseases such as arthritis, glycaemic index, and fatty liver syndrome. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…Esculetin has been shown to have therapeutic effects in a variety of conditions, including free radical scavenging, suppression of various dysregulated transcription factors in cancer, and effects on inflammatory pathways involved in diseases such as arthritis, glycaemic index, and fatty liver syndrome. [17] Due to the effects of esculetin on various systems, this study looked at the effects of esculetin on a rat ovarian I/R injury model. To our knowledge, there are no studies investigating the effects of esculetin on ovarian I/R injury.…”
mentioning
confidence: 99%
“…Natural products with novel structures are an important source of anti-cancer candidates. Esculetin (Esc) is a natural simple coumarin, which has a variety of pharmacological activities, such as anti-inflammatory, anti-tumor, , anti-oxidant, and so on . Esc can increase the expression of cyclophilin D (CypD) within cancer cells, leading to the opening of the mitochondrial permeability transition pore (PTP) .…”
Section: Introductionmentioning
confidence: 99%
“…Esculetin (Esc) is a natural simple coumarin, which has a variety of pharmacological activities, such as anti-inflammatory, 4 anti-tumor, 5,6 antioxidant, 7 and so on. 8 Esc can increase the expression of cyclophilin D (CypD) within cancer cells, leading to the opening of the mitochondrial permeability transition pore (PTP). 9 This process results in the release of pro-apoptotic proteins from the mitochondria and triggers cancer cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Esculetin has been shown to have many pharmacological activities in vitro and in vivo, including antioxidant, anticancer, anti-inflammatory, antidiabetic, anti-atherosclerotic, and so on. [6][7][8] A recent study demonstrated that administration of esculetin ameliorated intestinal inflammation and reduced serum levels of the pro-inflammatory cytokines such as tumor necrosis factor alpha (TNF-α), interleukin-1β (IL-1β), and IL-6 in a mouse model of dextrose sodium sulfate (DSS)-induced UC. [9] However, the mechanism by which it protects against UC remains to be discovered.…”
Section: Introductionmentioning
confidence: 99%